Pengaruh Metode Circuit Training Terhadap Kemampuan Vo2max Dalam Permainan Sepakbola Siswa Smpn 1 Tambelang - ridoni, rahmat; Kurniawan, Febi; Gustiawati, Resty (Peneliti.net, 2024)
Physical condition is a prerequisite that is very necessary in efforts to increase the performance of an athlete, it can even be said to be a basic necessity that cannot be postponed or negotiated. The purpose of this study was to determine the effect of the Circuit Training method on the extracurricular soccer VO2MAX abilities of students at SMPN 1 Tambelang. Quantitative research methods can be interpreted as research methods based on the philosophy of positivism, used to examine certain populations or samples, data collection uses research instruments, data analysis is quantitative/statistical in nature, with the aim of testing established hypotheses. The approach used in this study is a quantitative approach that focuses on its main objective, namely to find out whether there is an effect of the Circuit Training Method on VO2MAX Ability in Soccer Games for Students of SMPN 1 Tambelang. Sampling technique by means of Cluster Random Sampling. According to P. Kurniawan, (2016: 69) Cluster Random Sampling is a random sampling technique that is selected based on groups. In this study, students at SMPN 1 Tambelang were used as samples. Results of the discussion There is a significant effect of circuit training on the ability of VO2MAX. This can be known by conducting research. Research knowing the initial conditions at the pretest obtained the highest value of VO2MAX obtained was 36.7 and for the lowest value was 29.92 and the average value was 33.322. Meanwhile, after carrying out the treatment or research, the posttest scores for circuit training learning outcomes increased with the highest VO2MAX score being 37.4, the lowest score being 30, and the average score being 34.022.